Estimation of the possibilities of the combined synchronization system with open-link to minimize the dispersion of the phase error when tracking the carrier frequency under the conditions of the influence of additive noise - Turovsky, Olexandr (Technology audit and production reserves, 2020)
The object of the article is the process of evaluating the possibilities of a combined synchronization system with open (compensating) connection to minimize the phase error variance under the influence of additive Gaussian noise. The issue of improving the quality of the phase synchronization system is a constant topical scientific task and in a number of studies is solved by including the method of developing mathematical models and creating on their basis the appropriate optimal schemes for building these systems. The final stage of development and implementation of such mathematical models in technical solutions and synchronization schemes based on them is the assessment of the limit possibilities of these schemes to minimize the variance of the phase error in different types of noise The paper evaluates the possibilities of a combined synchronization system with open (compensating) connection to minimize the phase error dispersion under the influence of additive Gaussian noise by selecting the parameters of the components of the circuit of this connection. In order to evaluate the work, mathematical dependencies have been developed and refined, which allow to determine the variance of the phase error under the influence of additive Gaussian noise and the corresponding algorithm for its determination is presented. The evaluation results presented in the work showed that the value of the error variance for the combined synchronization system is much smaller than for the closed synchronization system with any choice of the parameters of the latter. The effect of reducing the phase error variance by introducing a broken link at a given level of influence depends on the noise signal level and the phase modulation index of the input signal. When using as a simple broken link a frequency discriminator included in the circuit of the combined synchronization system in parallel, the minimum dispersion of the phase error when the noise level rises to a certain critical limit is limited and this broken link loses its effectiveness.